Leisure physical exercise and creatine kinase activity. The Tromsø study - Bekkelund, Svein Ivar (Scandinavian Journal of Medicine & Science in Sports, 2020)
Creatine kinase (CK) is an enzyme catalyzing energy reaction in muscle cells and has proven to modify cardiovascular risks. The influence of skeletal muscle activity on CK concentrations is a potential study confounder but is mainly reported in connection with sport activities. This study investigated the association between leisure physical exercise and CK and estimated the effect of physical exercise on the CK values. CK and leisure physical exercise defined as intensity, frequency, and duration subsets were measured in the population‐based Tromsø study. Comparisons of CK at different exercise levels, multivariate analyses, and relative differences in CK between “never exercise” and “heavy exercise” (moderate or hard exercise ≥2 hours per week) subgroups were analyzed age‐ and sex‐stratified in 12 796 men and women. CK increased significantly with higher levels of physical exercise intensity and frequency in both sexes analyzed by ANOVA. In a multivariate analysis, CK was independently associated with heavy exercise after adjusting for age, BMI, and blood pressure; OR 9.38 (95% CI 5.32‐16.53), P < .0001 in men and OR 5.20 (95% CI 2.53‐10.69), P < .0001 in women. The differences in CK between physically inactive and participants performing heavy exercise varied between 3.1% (women) and 6.4% (men) and was also larger in participants ≥50 years. In conclusion, CK was positively and independently associated with increasing leisure physical exercise in a general population. CK values associated with exercise were approximately twice as high in men than women, but exercise altered CK only modestly.